Hubungan Kepatuhan Konsumsi Tablet Fe terhadap Kejadian Anemia pada Ibu Hamil Trimester II di PKM Dumagin, Kabupaten Bolaang Mongondow Selatan - Robot, Silva; Ilmiah, Widia Shofa (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Anemia during the second trimester of pregnancy is a common hematological disorder that may affect both maternal and fetal health. This study aimed to analyze the relationship between adherence to iron tablet consumption and the incidence of anemia among second-trimester pregnant women. A cross-sectional design was applied with a total of 45 participants. Data were collected through structured interviews and hemoglobin documentation from maternal health records. Adherence was classified as high, moderate, or low, and anemia was categorized as mild, moderate, or severe. The results showed that 60% of respondents demonstrated high adherence, and the same proportion experienced mild anemia. Spearman Rank test revealed a very strong relationship between adherence and anemia (r = –0.875; p = 0.000). The findings indicate that higher adherence correlates with lower anemia severity. The success of iron supplementation programs depends on consistent behavior, health worker support, and family involvement. This study is limited in geographical scope and sample size, warranting cautious interpretation. Future research should explore behavioral, nutritional, and social determinants more comprehensively.